2017
DOI: 10.1080/09638288.2017.1393111
|View full text |Cite
|
Sign up to set email alerts
|

Falls among full-time wheelchair users with spinal cord injury and multiple sclerosis: a comparison of characteristics of fallers and circumstances of falls

Abstract: The results from this study helped to understand fall circumstances among full-time wheelchair users with MS and SCI. Findings from this study can inform the development of evidenced-based interventions to improve the effectiveness of clinically based treatment protocols. Implications for rehabilitation Falls are a common health concern in full-time wheelchair users living with multiple sclerosis and spinal cord injury. The circumstances surrounding falls reported by full-time wheelchair users living with mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 25 publications
2
34
0
5
Order By: Relevance
“…When developing fall prevention interventions, attention should move beyond single factor solutions to account for the multifactorial nature of falls. Findings from a prior study support this approach to fall prevention as the authors found 70% of falls were caused by more than one fall attribution 1. In clinical practice, healthcare practitioners should consider whether individuals with SCI who are primarily wheelchair users also ambulate short distances, as wheelchair users can experience falls during standing/walking 1 8.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…When developing fall prevention interventions, attention should move beyond single factor solutions to account for the multifactorial nature of falls. Findings from a prior study support this approach to fall prevention as the authors found 70% of falls were caused by more than one fall attribution 1. In clinical practice, healthcare practitioners should consider whether individuals with SCI who are primarily wheelchair users also ambulate short distances, as wheelchair users can experience falls during standing/walking 1 8.…”
Section: Discussionmentioning
confidence: 93%
“…Wheelchair users commonly experience falls during transfers, reaching, propelling on an uneven surface, moving in bed and showering 1 2 5 6. Depending on the level and severity of their SCI, some individuals primarily use a wheelchair for mobility but can also walk short distances 7.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,29,59 It is likely that the circumstances associated with falls differ amongst those who are ambulant or wheelchair users with one study suggesting that most falls occur during transfers for wheelchair users. 60 An additional method to uncover risk factors of falls in MS can be achieved by asking the individual what they attribute their falls to. According to Matsuda et al, 29 , pwMS attribute their falls to trips/slips, fatigue, failing to use an assistive device when needed, rushing and not paying attention.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%